An experimental study on dyeing of needle‐punched polyethylene‐terephthalate non‐wovens. (14th February 2021) - Khawar, Muhammad Tauseef; Tausif, Muhammad; Ashraf, Munir; Ahmad, Faheem; Ahmad, Sheraz; Azam, Farooq; Khattak, Mehran
Abstract: The dyeing of non‐wovens in fabric form is of interest for a range of applications especially aesthetics. In this work, needle‐punched non‐woven fabrics were prepared by employing polyethylene‐terephthalate (PET) fibres of two different linear density and same mean fibre length in four different fibre linear density ratios and three different fabric mass areal densities, while keeping all other process and material variables constant. The objectives of the study were to find out the saturation point in the dyeing profile of needle‐punched non‐wovens by varying aforementioned process variables and, for the first time, compare different industrially relevant conventional fabric dyeing methods (Jet, Package and Jigger dyeing) in terms of physical, mechanical and colour fastness properties. In case of Jet and Package dyeing, non‐woven fabric was successfully dyed without any structural reorientation while fabric sample deformation is reported in Jigger dyeing process. Furthermore, tensile strength (in newtons) of samples was increased, while air permeability (in mm/s) was decreased due to the slight compactness of structure after the dyeing process.